Checklist of the helminths of the kelp gull, Larus dominicanus (Aves: Laridae), with new records from Chile - Cerda, Fabiola; López, Juana; Ortega, René; Mathieu, Christian; Kinsella, Mike (Zootaxa, 2009)
Kelp gulls (Larus dominicanus) have a circumpolar distribution in the southern hemisphere. Their range extends as far north as Ecuador and they occur along the southern coast of South America and Africa as well as Australia, New Zealand and sub-Antarctic Islands. This study presents a checklist that summarizes sites of infections, localities, life cycles and their intermediate hosts (if known), and the pertinent references to demonstrate the wide diversity of kelp gull parasitic helminths. Our review of the existing literature (59 publications) on kelp gull parasites provided information on a total of 21 families and 49 genera, including 62 described species, of which 36 were described in Argentina, 21 in Chile, 12 in Antarctica, 11 in New Zealand, 7 in Brazil and 3 in South Africa. In addition, 11 parasites are recorded from Talcahuano, Chile, 10 of them are new records for Chile and 4 represented new host records, Aporchis sp., Maritrema eroliae, Microphallus nicolli and Tetrameres skrjabini.